Defect Size Comparison Using Infrared Thermography Method and Actual Measurement On Glass Fiber Reinforced Polymer - Jamil, Muhammad Hanif (Research Progress in Mechanical and Manufacturing Engineering, 2023)
There are three types of specimens have been inspected using Infrared thermography and one of the specimen is perfectly patched without any defect in the specimen and the remain two specimen has defect during patching. Active infrared thermography approaches is used by using heat gun to the surface of specimen with temperature 200°C. Thermal image for specimen B1 shows no defect occur while specimen B2 and B3 show defect in the specimen. The defect dimension in thermal image are been measured using ImageJ software after analyzed in FLIR Tools software. Surface of the specimen have been grind to reveal the defect and actual dimension have been measure to be compare. The result of the comparison dimension defect are being analyzed and explained in this study.